Application of Group Counseling Stress Inoculation Training Techniques in Overcoming the Stress of Working on a Thesis Students - Harris, Mayrisa Khadijah (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
This study aims to apply group counseling to the Stress Inoculation Training technique in dealing with the stress of working on a thesis on Counseling Guidance students. This type of research is quantitative research with a Pre-Experimental Design approach. The subjects in this research were 8 2019 Stambuk counseling students. This research consisted of 4 meetings. The results of the research showed that the average pre-test and post-test score for students' stress coping skills was 107.37 and after being provided with the service it decreased drastically. to 74.25. This means that the average value of overcoming student stress has decreased after being given service. Based on the results of the Wilcoxon test, the result is that ð½â„Žð‘–ð‘¡ð‘¢ð‘› ð‘” > ð½ð‘¡ð‘Žð‘ð‘’ð‘™ where 6 > 4, which means the hypothesis in this research is accepted. Based on the data above, it can be concluded that the stress coping skills of 8 guidance and counseling students at Medan State University who were working on their thesis before being given the stress inoculation training technique group counseling service were found to be high, after being given the stress inoculation training technique group counseling service their stress coping skills were reduced.